Measuring Team Effectiveness in the Health Care Setting: An Inventory of Survey Tools - Bita A Kash; Ohbet Cheon; Nicholas M Halzack; Thomas R Miller (SAGE Publishing, 2018)
Background: Guidance for measuring team effectiveness in dynamic clinical settings is necessary; however, there are no consensus strategies to help health care organizations achieve optimal teamwork. This systematic review aims to identify validated survey instruments of team effectiveness by clinical settings. Methods: PubMed, MEDLINE, and ISI Web of Knowledge were searched for team effectiveness surveys deployed from 1990 to 2016. Validity and reliability were evaluated using 4 psychometric properties: interrater agreement, internal consistency, content validity, and structural integrity. Two conceptual frameworks, the Donabedian model and the Command Team Effectiveness model, assess conceptual dimensions most measured in each health care setting. Results: The 22 articles focused on surgical, primary care, and other health care settings. Few instruments report the required psychometric properties or feature non-self-reported outcomes. The major conceptual dimensions measured in the survey instruments differed across settings. Team cohesion and overall perceived team effectiveness can be found in all the team effectiveness measurement tools regardless of the health care setting. We found that surgical settings have distinctive conditions for measuring team effectiveness relative to primary or ambulatory care. Discussion: Further development of setting-specific team effectiveness measurement tools can help further enhance continuous quality improvements and clinical outcomes in the future.